2019
DOI: 10.1242/dev.174367
|View full text |Cite
|
Sign up to set email alerts
|

Paxillin-dependent regulation of apical-basal polarity in mammary gland morphogenesis

Abstract: Establishing apical-basal epithelial cell polarity is fundamental for mammary gland duct morphogenesis during mammalian development. While the focal adhesion adapter protein paxillin is a well-characterized regulator of mesenchymal cell adhesion signaling, F-actin cytoskeleton remodeling and single cell migration, its role in epithelial tissue organization and mammary gland morphogenesis in vivo has not been investigated. Here, using a newly developed paxillin conditional knockout mouse model with targeted abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 70 publications
(90 reference statements)
3
19
0
Order By: Relevance
“…Since paxillin did not significantly affect tumor growth, as shown by ki67 staining (Figure S1, B and C), which is consistent with the study showing that in normal mouse mammary gland the proliferation and apoptosis rate is not altered by paxillin knockout (Xu et al, 2019), we assessed whether distant metastasis is impacted by paxillin expression. H&E staining of lung sections and analysis of the surface of the whole lungs from the PyMT tumor mice revealed that the paxillin KO lungs have fewer lung metastases, as compared to paxillin WT lungs (Figure 1, E-G).…”
Section: Paxillin Facilitates Lung Metastasis In Mouse Breast Tumor Progressionsupporting
confidence: 88%
See 4 more Smart Citations
“…Since paxillin did not significantly affect tumor growth, as shown by ki67 staining (Figure S1, B and C), which is consistent with the study showing that in normal mouse mammary gland the proliferation and apoptosis rate is not altered by paxillin knockout (Xu et al, 2019), we assessed whether distant metastasis is impacted by paxillin expression. H&E staining of lung sections and analysis of the surface of the whole lungs from the PyMT tumor mice revealed that the paxillin KO lungs have fewer lung metastases, as compared to paxillin WT lungs (Figure 1, E-G).…”
Section: Paxillin Facilitates Lung Metastasis In Mouse Breast Tumor Progressionsupporting
confidence: 88%
“…We have previously reported that paxillin is required for normal mouse mammary gland morphogenesis and development in a mammary epithelial cell-specific MMTV-cre-mediated paxillin conditional knockout mouse (Xu et al, 2019). Herein, this mouse line was bred with the MMTV-PyMT tumor mouse model in order to evaluate paxillin function in breast tumor progression.…”
Section: Paxillin Facilitates Lung Metastasis In Mouse Breast Tumor Progressionmentioning
confidence: 99%
See 3 more Smart Citations